IMPLEMENTASI KEBIJAKAN PENGHIJAUAN KOTA DI SAMARINDA - Muchlis Gustiawan; Syahrani (Journal of Policy & Bureaucracy Management, 2020)
Urban greening is an activity to fill environmental open spaces in dealing with the environmental crisis amidst the rapid development. Public green open spaces in Samarinda City which only reaches 4,62 percent of the total area of Samarinda City, in addition to the low awareness of the people of Samarinda City in protecting green plants and protective trees. This research describes the implementation of Samarinda City Regional Regulation Number 19 of 2013 concerning Urban Greening and its inhibiting factors by using a qualitative descriptive approach. Cutting and pruning of reforestation plants including the transportation of the results of logging and burning due to lack of socialization to the community. Inhibiting factors for urban greening in Samarinda include the lack of supporting facilities for the implementation of greening, the lack of community awareness of urban greening and the inconsistency of community reports to the City Government of Samarinda regarding urban greening.